Performance of cognitive tasks and functional brain activity in anxiety disorders - A. V. Kirenskaya; E. V. Fedorova; K. Yu. Telesheva; A. M. Gonopolsky; A. M. Chernorizov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2024)
Objective. To improve understanding of psychophysiological underpinnings of anxiety disorders a comprehensive study, that included the analysis of cognitive tasks performance, event-related potentials and psychometric scales, has been conducted.Materials and Methods. Participants were patients with generalized anxiety disorder (GAD group — 12 s.), mixed anxiety and depressive disorder (ADD group — 16 s.) and healthy volunteers (control group — 16 s.). The psychometric techniques included the questionnaires of Spielberger, HADS (Hospital Anxiety and Depression Scale) and Carver-White (BIS/BAS Scale). Psychophysiological methods included antisaccade task (AS) and event-related evoked potentials P300 that were recorded during auditory oddball task.Results. The significantly increased anxiety and depression scales, as well as the decreased BAS Reward Responsiveness scale, was found in patients of both clinical groups compared to control one; the increased BIS scale was revealed only in ADD group. In GAD and ADD groups AS performance was worse in response to stimuli in left hemi-field that are initially processed in right hemisphere; on the contrary, decreased number of target stimuli omissions was found in oddball task in clinical groups. P300 amplitude was larger, and P300 latency was shorter for patients with ADD compared to controls. Analysis of asymmetry demonstrated that P300 amplitudes were greater over the frontal-central right than over the left hemisphere in ADD group.Conclusion. The study demonstrated that anxiety disorders are accompanied by reallocation of attentional resources and changes in functional organization of brain networks involved in attention and executive functions. With the same direction, the shifts were greater in ADD group.